Evaluation of menstrual cycle effects on morphine and pentazocine analgesia - Ribeiro-Dasilva, MC (2011)
Studies have demonstrated menstrual cycle influences on basal pain perception, but direct evidence of menstrual cycle influences on analgesic responses has not been reported in humans. Our aim was to determine whether the magnitude of morphine and pentazocine analgesia varied across the menstrual cycle. Sixty-five healthy women, 35 taking oral contraceptives (OC) and 30 normally cycling (NOC), underwent experimental pain assessment both before and after intravenous administration morphine (0.08 mg/kg) or pentazocine (0.5 mg/kg) compared to saline placebo. Both active drug and placebo were administered once during the follicular phase and once during the luteal phase. Measures of heat, ischemic and pressure pain sensitivity were obtained before and after drug administration. Change scores in pain responses were computed to determine morphine and pentazocine analgesic responses, and medication side effects were recorded. The data were analyzed using mixed-model ANOVAs. NOC women showed slightly greater heat pain sensitivity in the follicular vs. luteal phase, while the reverse pattern emerged for OC women (p=0.046). Also, OC women showed lower pressure pain thresholds compared to NOC women (p < .05). Regarding analgesic responses, NOC women showed greater morphine analgesia for ischemic pain during the follicular vs. the luteal phase (p=0.004). Likewise, side effects for morphine were significantly higher in NOC women in the follicular phase than in the luteal phase (p=0.02). These findings suggest that sex hormones may influence opioid responses; however, the effects vary across medications and pain modalities and are likely to be modest in magnitude.